Ecological bases for biological control - Fowler, Harold G.; di Romagnano, Ligia F. T. (Pesquisa Agropecuaria Brasileira, 1992)
The ecological bases of biological control are reviewed, and, in particular predation theory and predator searching patterns. Recent literature suggests that many of the common rules of thumb used in biological control of insect and plant pests do not fully follow established dogma. Furthermore, we question the ecological stability of large scale microbiological pest control, which we find to be evolutionarily risky, leading to the rapid appearance of resistant pests. In fact, we argue that microbial control as currently practiced differs little from standard chemical control programs, due principally to the lack of epidemiological understanding of the system being worked. Recent findings based upon hierarchy and percolation theory may allow us to explain why some biological control programs do not work, as well as explain the apparent discrepancy between. small scale field tests and large scale liberations. Chief among the current problems are integrating spatial and temporal sales of variation into theoretical strategies of natural enemies, both behaviorally and evolutionarily.